Birch Pollen Deposition and Transport along an Altitudinal Gradient in the Bavarian Alps—A Case Study Using Gravimetric Pollen Traps in the Pollen Season 2020 - Wörl, Verena; Jetschni, Johanna; Jochner-Oette, Susanne (Atmosphere, 2022)
There is only little and partially contradicting knowledge on the variation of pollen abundance at different altitudes in mountainous regions. The aim of this work is to gain new insights on the influence of wind and surrounding trees on the deposition and transport of birch (Betula spec.) pollen in the Bavarian Alps, Germany. Data on birch pollen deposition were collected at five sites using gravimetric traps along an altitudinal gradient from Garmisch-Partenkirchen (720 m a.s.l.) to the Environmental Research Station Schneefernerhaus (2650 m a.s.l) in the pollen season 2020. We compared these data with birch pollen concentration derived from a volumetric trap at Schneefernerhaus and with phenological data, i.e., flowering onset times observed at 21 birch trees at different altitudes. Wind data were gathered directly at or near each pollen trap and surrounding birch trees were mapped in the field. Whereas the pollen load was lowest at the highest location, substantially higher values were measured at medium altitudes (1300–1600 m a.s.l.). This can be explained by the pronounced mountain-valley wind system, which ensured the transport of pollen to the corresponding altitudes. We conclude that pollen levels are influenced by topography, local wind systems and the availability of pollen. Pollen levels in complex mountainous environments are therefore not substantially affected by the occurrence of birch trees in the immediate vicinity.